Shaping ways of managing diversity in Portuguese schools from the student's perspective - Caetano, P.; Mendes, M. (International Review of Sociology, 2014)
This article examines the results of an empirical research project that analysed the political socialisation processes of the students at three Portuguese public secondary schools in the Lisbon Metropolitan Area in 2011. Against the background of the implementation of an 'education for citizenship' programme in the official Portuguese school curriculum (2001), the project basically sought to know what attitudes the students mobilised in the face of a hypothetical situation involving the presence of ciganos (gypsies) in a school context. In this respect, and based on a pragmatic and comprehensive perspective, we attempted to test the concept of multiculturality and how it is seen and experienced by the students at these schools. Our aim is to answer the question: In a school context, how do students think the coexistence of gypsies and non-gypsies should be managed? In seeking to answer this question, the methodology that seemed to us most appropriate to this study's objectives is founded on the mobilisation of a scenario-based questionnaire, and to this purpose we surveyed 700 secondary students in a classroom environment. We were able to identify and characterise four possible coexistence formats within the overall framework of a synoptic vision of the available ways of managing a multicultural experience: separation; socialisation; universalism; and co-operation